(untitled) (Journal of the College of Basic Education, 2022)
The current study aimed to evaluate the effect of the heavy metals copper, cadmium and cobalt when added individually, in combination and in combination on the growth and reproduction of the aquatic fungus Saprolegnia hypogyna.